Five New Species of Wood-Decaying Brown-Rot Fungi within Postiaceae (Polyporales, Basidiomycota) from Xinjiang, Northwest China - Tai-Min Xu; Dong-Mei Wu; Neng Gao; Long Zeng; Yi-Hua Xu; Xiang-Ping Fan; Yi-Fei Sun; Bao-Kai Cui (Journal of Fungi)
Brown-rot fungi are an important group of wood-decaying fungi, but there has been limited research on the species diversity of brown-rot fungi in Xinjiang, China. During an investigation of brown-rot fungi in Xinjiang, from July 2018 to July 2023, five new species belonging to the family Postiaceae were discovered based on morphological and molecular evidence. Amaropostia altaiensis is characterized by a conchate pileus, circular pores (5–8 per mm), and growing on Populus. Amaropostia tianshanensis is characterized by a flabelliform-to-conchate pileus, angular pores (5–6 per mm), and growing on Picfea. Cyanosporus latisporus is characterized by a hirsute and dark greyish blue pileal surface with fresh, larger pores (3–6 per mm) and broad basidiospores (4.3–5.9 × 1.4–2 µm). Cyanosporus tianshanensis is characterized by a smooth and white-to-cream pileal surface with fresh, smaller pores (6–9 per mm). Osteina altaiensis is characterized by a light mouse-grey-to-honey-yellow pileal surface, smaller pores (4–6 per mm), and slightly wide basidiospores (5–6 × 1.7–2.2 µm). Each of these five new species form independent lineages in phylogenetic analyses based on the seven gene loci (ITS + nLSU + nSSU + mtSSU + TEF1 + RPB1 + RPB2). This research enriches the diversity of brown-rot fungi species, while also demonstrating the substantial discovery potential and research value of brown-rot fungi in Xinjiang.